Clinical and Bacteriological Profile of Early Onset Neonatal Sepsis Admitted in NICU of Tertiary Hospital in Biratnagar - Giri, Arun; Sah, Vijay Kumar; Poudel, Bikash Sharma; Niraula, Niraj; Sedai, Raju (Birat Journal of Health Sciences, 2018)
Introduction: Neonatal sepsis is one of the major causes of neonatal morbidity and mortality especially in developing countries. The clinical signs and symptoms of neonatal sepsis are non specific and blood culture report is considered gold standard for confirmation of neonatal sepsis. Organisms and their sensitivity pattern vary from place to place. The confirmation of diagnosis and management of neonatal sepsis is challenging and time consuming. Objective: The aim of this study was to find incidence of blood culture proven sepsis in suspected early onset neonatal sepsis, find out sensitivity pattern of isolated organism and to find association of risk factors and clinical signs and symptoms with blood culture proven sepsis. Methodology: Prospective study was conducted in Nobel Medical College, Biratnagar from November 2016 to November 2017. Sample size was calculated to be 300 and blood culture was sent of each neonates admitted with suspected early onset neonatal sepsis before giving neonates with first dose of antibiotics and report of 72 hours was taken into consideration. Results: Out of 300 cases of suspected early onset neonatal sepsis 70.3% presented with lethargy, followed by other symptoms like poor feeding, respiratory distress, fever, hypothermia, feeding intolerance, abnormal body movement and abdominal distension. Low birth weight neonates, preterm neonates, prolonged duration of per vaginal leaking and low platelets count were significantly associated with blood culture proven sepsis in this study. Incidence of blood culture positive sepsis in suspected early onset neonatal sepsis was 27%. Coagulase negative Staphylococcus aureus(21%) was predominant organism isolated followed by Klebsiella Pneumonia, Pseudomonas, Escherichia coli. All of the isolated Klebsiella and Pseudomonas and 86% of Escherichia coli were found to be resistant to ampicillin. All isolated Coagulase negative Staphylococcus aureus were sensitive to vancomycin. Conclusion: Coagulase negative Staphyloccus aureus was predominant organism detected but majority of organisms were gram negative organisms. High resistance to ampicillin was found and cefotaxime was also less sensitive to isolated organism. Vancomycin was found to be sensitive to all isolated Staphylococcus aureus and coagulase negative Staphylococcus aureus. Amikacin was highly sensitive among causative organisms isolated. BJHS 2018;3(1)5 : 370-376